Genetic diagnosis of Mendelian disorders via RNA sequencing - Laura S. Kremer (Nature Portfolio, 2017)
Genome sequencing alone fails to provide a genetic diagnosis for many Mendelian disorder patients. Here, the authors utilize RNA sequencing to complement genotyping of patients with a rare mitochondrial disease by detecting aberrant RNA expression, splicing and allele-specific expression.